Estudo avaliativo sobre planejamento, execução e controle de projetos de pesquisa em instituição de ensino superior pública - Danzer, Valter Gustavo (2021)
The objective of this research consists in conducting an assessment of the ways and methods in which research projects are planned, executed and controlled in a Higher Education Institution (HEI), namely: Universidade do Estado de Mato Grosso (Unemat), in which there are several initiatives that have demanded differentiated approaches in their management process. Scientific production, in studies carried out by Higher Education Institutions, demands projects that have an integrative, interdisciplinary methodology, aligned with the institutional objectives and that have flexibility in their planning, considering the path to be followed for the intended result. In the theoretical references it is identified that the existing methodologies have their forms directed to specific groups of product and/or process production. For the process of aligning the actions necessary for the development of research projects, it was necessary to design a way to approach the magnitude of the problem to be diagnosed and the ways to face it. The research can be classified as escriptive, considering that it seeks as much information as possible from a specific group, adding extra information by its interpretation, and has a quantitative approach, considering that it is characterized by data collection through a specific instrument. By means of a questionnaire, professors who are members of the Post-Graduation programs (PPG) of the Universidade do Estado de Mato Grosso (Unemat), with notorious production in research activities at the institution, were consulted. By the analysis of the collected data, the experiences of the respondents and the deficiencies pointed out in the management process of research projects in the institution were identified. The research points out that 42% of the respondents stated that they are 'never' or 'rarely' charged with methods of planning, execution and control of results in research projects. With these results it is possible to identify the lack of diffusion of methods and/or standards for the research faculty of a Higher Education Institution. We also identify that 75% of the respondents do not feel fully supported by technological tools that support them in the governance of research projects. From the results of this academic-scientific research, we obtained a comparative study and the presentation of a proposal for an agile methodology involving the methods Objectives and Key Results (OKR), Scrum, Kanban and Project Management Body of Knowledge (PMBOK), directed to research projects in Higher Education Institutions. Finally, for future contributions, there is the possibility of applicability of the proposed methodology in research projects and the construction of indicators of its execution viability.